A retrospective analysis of the risk factors leading to perinatal mortality at a tertiary care hospital of Sikkim, India - Rai, Chanda; Kharka, Latha V.; Dutta, Sudip; Kumar, Nishant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study helps to assess the burden of perinatal mortality at a tertiary referral hospital in Sikkim known for its hilly terrain which makes health services difficult to access. The aims and objectives were to determine the various causes and risk factors leading to perinatal mortality in order to formulate preventive strategies Methods: All perinatal deaths over a year between August 2016-2017 were included and analysed in our study. Results: A stillbirth rate of 14 per 1000 total births and early neonatal death rate of 8 per 1000 live births was found in 1855 total births. Complications related to pregnancy like pre-eclampsia (16%), eclampsia (8%), ante-partum haemorrhage (15%) and medical disorders (13%) were major contributors to stillbirths while pre-maturity (53.3%), sepsis (20%), birth asphyxia due to meconium aspiration (13.3%) were notable factors leading to early neonatal deaths. In majority of the cases, factors like poor literacy, low socio-economic status, increased basal metabolic index and inadequate ante-natal care caused increased perinatal losses. Conclusions: Perinatal grief continues to surround women who have suffered perinatal deaths and serious efforts should be made to bring down the mortality rates by improving health , nutrition of all expecting mothers and increase their awareness to seek ante-natal health services in order to avoid any catastrophe in terms of maternal and fetal loss.